MENGAPA TENAGA PENGAJAR PRODI KEPERAWATAN DI YOGYAKARTA TIDAK MEMENUHI STANDAR AKREDITASI BAN PERGURUAN TINGGI? - Nurul Isnaini F.; Hari Kusnanto; Mubasysyir Hasanbasri (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: The main factor that determines the quality of education in higher education is the quality of the lecturers in it. Quality nursing services need to be supported by nursing resources that are produced from quality educational institutions according to established standards. In fact, the current nursing education does not have a national standard so that the quality of its graduates varies. Objective: This study aimed to describe and determine the characteristics of the lecturers that include educational qualifications, functional, certification, and the ratio of faculty in nursing studies program and see the extent to which faculty contribute to meet the accreditation status of private nursing studies program in Yogyakarta. Methods: Analysis of a cross sectional quantitative data by univariate analysis. Result: The status of accreditation in private nursing courses in Yogyakarta (40%) accreditation of B and (60%) accredited programs C. length stand of Nursing program did’nt show evidence of accreditation better. Based on the educational qualifications of teachers who are eligible according to the standard Accreditation B (35%), which does not meet the standards yet accredited B (5%), the variable functional and no lecturer certification courses that meet the standards of BAN PT. The ratio of lecturers in private nursing studies program is still not ideal proved to be only 10% of nursing study program that has a good ratio. From observations and interviews obtained evidence several nursing program still face many obstacles in improving the quality of human resources and implementation of accreditation. Conclusion: The status of accreditation of private nursing in Yogyakarta is still low, faculty of Nursing Prodi also still don’t meet the qualifications in accordance with Law 14 of 2005. It takes a strong commitment from study program organizers and the government to foster private nursing colleges in Yogyakarta.